Effect of Intercropping of Cotton and Peanut on Quantity and Quality of Soil Microorganisms (Eurasian Scientific Herald, 2022)
The effect on the increase in the number and quality of soil microorganisms under the conditions of co-planting of cotton with peanut in the conditions of sandy soils of the desert region is highlighted.